Prevalência e fatores associados à hipertensão arterial sistêmica autorreferida entre trabalhadores da prefeitura de Goiânia - Aleixo, Lidia Morais Santos Barreira (2015)
Prevalence and factors associated with self-reported high blood pressure among public workers of Goiania Municipality Worldwide, high blood pressure (HBP) is considered the most prevalent chronic disease and is associated with high cardiovascular and brain morbidity. Prevention, early diagnosis and proper treatment are essential to reduce the damage from HBP. The objective of this study is to estimate the prevalence and factors associated with high blood pressure, hypertension (HBP) among municipal public service workers. A cross-sectional study was conducted with data of the survey administered to all public workers of Goiania municipality in 2009. The survey was conducted electronically by the Human Resources of the municipality. The workers answered a structured questionnaire covering administrative, personal and health data. Logistic regression was used to investigate the association between HBP and sociodemographic and occupational variables, lifestyle and co morbidities. We calculated crude and adjusted Odds Ratio (OR). A value of p ≤ 0.05 was used for the analysis. We analyzed data from 30,566 workers who responded to the survey hypertension issues. The workers age ranged from 18 to 74 years, with a median of 41 years; 48.8% had a university degree; 34.8% were blue-collar workers; family income up to 3 minimum wage (50.4%) and 64.6% were women. The prevalence of self-reported HBP was 13.0% (95% CI 12.7 to 13.4). In multivariate analysis, hypertension was associated with female gender, age, middle education attainment, income above three minimum wages, occupation, self-report diabetes, fatigue report after working hours and emotional disorders history. These findings demonstrate the importance of psychosocial and occupational factors in the prevalence of hypertension in the civil service. The results may support HBP prevention programs aimed at improving the quality of life in the workplace, prioritizing the most vulnerable groups.